STUDI PERBANDINGAN KERANGKA KURIKULUM AFRIKA SELATAN DAN KURIKULUM MERDEKA: IMPLIKASI TERHADAP PENGEMBANGAN KURIKULUM NASIONAL INDONESIA - Theresia Monika Siahaan; Mulyono Mulyono; SB Waluya (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This study aims to analyze the Comparative Study of the South African Curriculum Framework and the Independent Curriculum: Implications for the Development of the Indonesian National Curriculum. Education systems and curricula on the African continent are characterized by tremendous diversity across 54 countries and shared challenges inherited from the colonial era. Historically, curricula in many African countries have often been adaptations of European-based subject models, but after independence, these countries have struggled to achieve better relevance, access, and quality. The results of this study were obtained through an analysis of official curriculum documents, learning guides, and a review of relevant literature from both countries. The analysis was conducted comparatively on the South African curriculum and the Independent Curriculum issued by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia (Kemendikbudristek, 2022). The discussion focused on three main aspects that reflect the core of modern curriculum design, namely: (1) the structure, objectives, and basic principles of the curriculum; (2) learning approaches, competency outcomes, and assessment systems; and (3) the implications of the comparative results for the future development of the Indonesian national curriculum.